A clinico-mycological study of dermatophytoses and their in-vitro sensitivity to antifungal drugs - Manjunath Kadnur; Shishira R Jartarkar; Girish Narayanaswamy; Ashwath S Manoj Kumar; Sheena Arora; Thushara Balakrishnan (Wolters Kluwer Medknow Publications, 2022)
Background: There is an increase in the frequency of resistant and recurrent dermatophyte infections in India. We undertook a study to isolate the organisms in different clinical presentations and to study their sensitivity to clotrimazole, miconazole, fluconazole, and griseofulvin. Aims: The aim of this article was to study the clinico-mycological pattern of dermatophytes and their in-vitro sensitivity to commonly used antifungals. Objectives: The objectives were as follows: (1) to study the clinico-mycological patterns of dermatophytosis and (2) to study the in-vitro sensitivity patterns of culture isolates to clotrimazole, miconazole, fluconazole, and griseofulvin. Materials and Methods: A total number of 48 patients were included in the study. The study period was from August 2019 to February 2021. Skin scrapings and nail clippings were inoculated in Sabouraud dextrose agar. Isolates were identified based on gross colony characteristics and microscopic morphology of their micro- and macroconidia and accessory structures. The isolates were then transferred to sterile distilled water in vials and stored. The clinical isolates stored in the stock solution were subcultured on to Potato dextrose agar. Then, the antifungal disks and Griseofulvin E strip were applied on to the plates. The zones of inhibition around the disks were measured and recorded. In the case of E strip, the minimum inhibitory concentration value is read from the scale in terms of µg/mL, where the ellipse edge intersects the strip. Results: The total number of cases included were 48. Commonest clinical presentation was co-occurrence of Tinea cruris and corporis (33%). Trichophyton mentagrophytes was isolated in 56% of cases. Isolates showed highest sensitivity to clotrimazole (87.5%) followed by miconazole (60.4%). Only 8.3% were sensitive to fluconazole and 37.5% were sensitive to griseofulvin. Conclusion: T. mentagrophytes is the causative organism in significant numbers of dermatophytic infections. Though broth dilution is the standard method for sensitivity assay of dermatophytes, disk diffusion method could become a more simple alternative.